Research progress on the cupping therapy along meridians in the treatment of constipation after stroke (循经拔罐治疗中风后便秘) - WANG Li (王丽); HUANG Chaoping (黄朝萍); WANG Fang (王芳); MA Xin (马欣); ZHANG Shuai (张帅); LI Yanmin (李艳敏); CHENG Jiangyan (程江艳); WANG Jing (王晶) (中西医结合护理)
Constipation is a common complication after stroke, affecting the prognosis and patient’s quality of life. Cupping therapy is guided by the meridian syndrome differentiation along the du-meridian and Shu-acupoints of the bladder meridian of Foot-Taiyang. Cupping therapy along meridians is an effective Traditional Chinese Medicine nursing technique for regulating heart, liver, spleen and lung function, dredging the channel, regulating the qi-blood, balancing Yin and Yang, and improing the symptoms of constipation. (便秘是中风患者常见并发症, 严重影响患者预后和生活质量。循经拔罐作用于督脉和足太阳膀胱经上对应五脏六腑的俞穴, 可调节心、肝、脾、肺、肾等脏腑功能, 疏通经络, 调节气血, 平衡阴阳, 以改善便秘。)